Finite Element Analysis and ANFIS investigation of seismic behavior of sandwich panels with different concrete material in two story steel building (Fracture and Structural Integrity, 2019)
This study aimed to apply sandwich panel in a two-story steel building to improve its behavior. Sandwich concrete panels consist of three basic components including wires, insulating layer and concrete cover. This research studied the behavior of sandwich panels by changing the Young's modulus of the concrete with Finite Element Method and evaluated the displacement, acceleration, and panel stresses. According to the results, increasing the Young's modulus of the concrete, the frame seismic behavior was improved. Using sandwich panels instead of conventional brick increased the building resistance against seismic load while decreasing the structure drift and acceleration. Increasing the Young's modulus of the shotcrete layer enhanced the behavior of the seismic panel. In addition, the results showed that the two-story building, which comprised of sandwich panels, had an appropriate performance against the seismic load. Ultimately, ANFIS was used to predict the response of the building under seismic loads. The effects of some variables such as Young's modulus of concrete, variations on the elevation and panel’s number on displacement and acceleration have been presented.
Keywords: Sandwich Panel; Finite Element Method; Young's Modulus; ANFIS; Seismic Load